Experimental and theoretical study of the surface-controlled dissolution of cylindrical particles. Application to solubilization of potassium hydrogen carbonate in hot dimethylformamide. - Forryan, C; Klymenko, O; Wilkins, S; Brennan, C; Compton, R (2005)
In this paper we present a mathematical model for the surface-controlled dissolution of cylindrical solid particles. This is employed to interpret experimental data published previously for the dissolution of potassium bicarbonate in dimethylformamide at elevated temperatures. Significant kinetic differences in assuming cylindrical rather than spherical shapes are reported with the former representing a closer approximation to the true shape of the particles as revealed by scanning electron microscopy. From the fits of experimental data to the cylindrical model for the surface-controlled dissolution, the dissolution rate constant, k, for the dissolution of KHCO(3) in DMF was found to be (9.6 +/- 1.6) x 10(-9) mol cm(-2) s(-1) at 100 degrees C, and the activation energy for the dissolution was 34.5 kJ mol(-1) over the temperature range of 60-100 degrees C. Comparison between cylindrical and spherical dissolution theory highlights the importance of considering the particle shapes for realistic modeling of surface-controlled dissolution kinetics.